Mother's Behavior in Exclusive Breastfeeding and Factors Affecting It in the Working Area of Air Dingin Padang Health Center - Erda Mutiara Halida; Feni Andriani (Universitas Andalas, 2021)
United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) recommends that children only be breastfed with breast milk (ASI) for at least six months in an effort to reduce child morbidity and mortality. Solid food should be given after the child is 6 months old, and breastfeeding continued until the child is two years old. Many factors will affect the success of exclusive breastfeeding including knowledge, education, occupation, problems with the mother's breast, and interest in formula milk promotion. This study aims to determine how the behavior of mothers in exclusive breastfeeding and the factors that influence it. This type of research is quantitative with a cross sectional study design. The independent variables of this study were education, mother's knowledge and husband's support, while the dependent variable is the mother's behavior in exclusive breastfeeding. The subjects in this study were all mothers who had babies aged 6-12 months with multistage sampling technique. The statistical test in this study used the Chi Square test. The results showed that there was no relationship between mother's knowledge and mother's education with mother's behavior in exclusive breastfeeding (p>0.05), and there was a relationship between husband's support and mother's behavior in exclusive breastfeeding (p=0.000)